Preparation method of glycidyl ether ester and DCP bi-crosslinked EAA and LDPE cable material

By adding specific crosslinking agents to LDPE and EAA, free radical and nucleophilic addition crosslinking of high-voltage cable materials are achieved, and the voltage-regulating fragments and electron deep traps are introduced in situ, solving the poor mechanical properties and small molecular aids of existing materials. The problem of agent migration significantly improves the mechanical and electrical properties of the material.

CN119431835AActive Publication Date: 2025-02-14HARBIN UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411557536.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-02
Publication Date
2025-02-14
Estimated Expiration
2044-11-02

AI Technical Summary

Technical Problem

The mechanical properties of existing high-voltage cable insulating materials are poor, and they need to add crosslinking agents to meet the basic usage requirements. However, after the pressure stabilizer of small molecules is mixed with XLPE, there will be problems of migration and equality.

Method used

Add DCP and 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester to LDPE and EAA to simultaneously cause radical cross-linking and nucleophilic addition cross-linking to LDPE and EAA, and the original The voltage-regulating fragments and electron deep traps are introduced to avoid the addition of excess small molecule additives.

Benefits of technology

It significantly improves the mechanical and electrical properties of cable materials, including tensile properties and DC breakdown properties, while simplifying the preparation process, reducing costs, and has the prospect of industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to a preparation method of a 4-(4-epoxy methoxyphenyl) benzoic acid glycidyl ester and DCP bi-crosslinked EAA and LDPE high-voltage direct-current cable material, and belongs to the field of high-voltage direct-current cable materials. The preparation method of the 4-(4-epoxy methoxyphenyl) benzoic acid glycidyl ester and DCP bi-crosslinked EAA and LDPE high-voltage direct-current cable material comprises the following steps: taking an ethylene acrylic copolymer EAA and low-density polyethylene LDPE as matrixes, taking a small-molecular epoxy compound 4-(4-epoxy methoxyphenyl) benzoic acid glycidyl ester and DCP as cross-linking agents, and carrying out cross-linking reaction to prepare the 4-(4-epoxy methoxyphenyl) benzoic acid glycidyl ester and DCP bi-crosslinked EAA and LDPE high-voltage direct-current cable material. And heating and pressurizing on a plate vulcanizing machine to obtain the double-crosslinking high-voltage direct-current cable material. The preparation method of the double-crosslinking high-voltage direct-current cable material is simple, and the direct-current breakdown performance and the tensile property of the high-voltage cable material are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing a glycidyl ether ester and DCP double cross-linked EAA and LDPE cable material, belonging to the technical field of high-voltage direct current cable material preparation. Background Art

[0002] Power cables not only provide reliable power supply for families and enterprises, but also support the normal operation of multiple fields such as industry, transportation, and communication. At present, the mainstream high-voltage cable insulation material is prepared by adding various small molecule additives such as voltage stabilizers and antioxidants based on low-density polyethylene as the matrix, wherein low-density polyethylene is the most important component to exert the insulation performance of the material. However, the mechanical properties of low-density polyethylene itself are poor, and it is necessary to form cross-linked polyethylene (XLPE) by adding peroxide crosslinking agent DCP to make its mechanical properties meet the basic use requirements. In order to meet the use standards of cable insulation materials, traditional cross-linked polyethylene will add functional additives such as voltage stabilizers and co-crosslinking agents to improve the withstand voltage grade and mechanical strength of the material, but after the small molecule voltage stabilizer is mixed with XLPE, there will be problems such as migration and phase separation, so the present invention proposes a new XLPE crosslinking method, while introducing polyolefin polymer substances in the system, the voltage stabilizing segment is introduced into the insulating material in a "click reaction" manner, and the purpose of improving mechanical properties and electrical properties is achieved at the same time.

[0003] The present invention adds two crosslinking agents, DCP and 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester, into LDPE and EAA, so that free radical crosslinking and nucleophilic addition crosslinking occur simultaneously between LDPE and EAA, and voltage stabilizing fragments and electron deep traps are introduced in situ during crosslinking, so that the mechanical properties and electrical properties of the cable material can be improved without adding extra small molecule additives. Summary of the invention

[0004] The invention discloses a method for preparing a 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester and DCP double crosslinked EAA and LDPE high-voltage direct current cable material, which is characterized in that a certain amount of low-density polyethylene (LDPE) and small molecule 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester, ethylene acrylic acid copolymer (EAA) and dicumyl peroxide (DCP) are added into a torque rheometer for melt blending to obtain a mixed material; the mixed material is pressed and formed in a flat vulcanizer, and then heated for crosslinking, and after cooling, a high-voltage direct current cable material with significantly improved breakdown strength and tensile properties is obtained, which is referred to as LEED.

[0005] Furthermore, the amount of DCP is 1.4% of the mass of LDPE, and the blend of 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester, EAA, and LDPE contains: 1%-7% by mass of EAA, 91.72%-98.82% by mass of LDPE, and 0.18%-1.26% by mass of 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester.

[0006] One of the purposes of the present invention is to provide a method for preparing the composite material, the method comprising the following steps:

[0007] S1, melt blending; blending all raw materials uniformly to obtain a DCP / epoxy / EAA / LDPE blended composite insulation material;

[0008] S2, processing and molding; the DCP / epoxy / EAA / LDPE blended composite insulation material is pressed and molded in a flat vulcanizer, and then cross-linked under pressure, and then vacuum dried after cooling to obtain the high-voltage DC cable material LEED.

[0009] Further defined, S1 is specifically: first add low-density polyethylene into a torque rheometer at 115°C and 50 rpm and mix for 5 minutes, then add EAA and epoxy compound and mix for 10 minutes, and finally add DCP and mix for no more than 3 minutes. After mixing evenly, DCP / epoxy / EAA / LDPE blended material can be obtained.

[0010] It is further defined that the pressing temperature in S2 is 115° C. and the pressure is 15 MPa.

[0011] It is further defined that the pressure cross-linking temperature in S2 is 175° C. and the pressure is 15 MPa.

[0012] It is further defined that the vacuum drying treatment temperature in S2 is 80° C. and the time is 24 h.

[0013] A second object of the present invention is to provide an application of the composite material mentioned above, specifically the composite material is used to make a high voltage DC cable.

[0014] The present invention has the following beneficial effects:

[0015] (1) The small molecule epoxy compound designed in the present invention can be cross-linked with a polymer containing a carboxyl group. The cross-linked EAA and XLPE can form a double cross-linked system, which can significantly improve the tensile properties of the material.

[0016] (2) The aromatic compound in the present invention can play a voltage stabilizing role, and the electron traps formed in situ can effectively capture electrons, significantly enhancing the DC breakdown performance of the high-voltage DC cable material.

[0017] (3) The LEED composite insulation material prepared by the present invention has a simple preparation process, low cost, and easy-to-obtain materials, and has a prospect for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Infrared spectrum test diagrams of LEED high voltage DC cable materials provided in different embodiments;

[0019] Figure 2 Thermal elongation diagram of LEED high voltage DC cable materials provided in different embodiments;

[0020] Figure 3 Tensile test result curves of LEED high voltage DC cable materials provided in different embodiments;

[0021] Figure 4 Weibull distribution diagram of DC breakdown field strength of LEED high voltage DC cable materials provided in different embodiments. DETAILED DESCRIPTION

[0022] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0023] Embodiment 1:

[0024] The process of preparing the LEED modified composite material in this example is as follows:

[0025] (1) Melt blending: 39.53 g of LDPE was added to a torque rheometer and melted at 115 °C with a rotation speed of 50 r / min. After mixing for 5 min, 0.4 g of EAA and 0.07 g of epoxy compound 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester (hereinafter referred to as E) were added and mixed for 10 min. Finally, 0.55 g of DCP was added and mixed for 3 min to obtain LE 1.0 ED 1.4 Blended composite materials.

[0026] (2) Processing: LE 1.0 ED 1.4 The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 minutes at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 1.0 ED 1.4 High voltage DC cable materials.

[0027] Embodiment 2:

[0028] (1) Melt blending: 38.58 g of LDPE was added to a torque rheometer, melted at 115 °C, with a rotation speed of 50 r / min, and mixed for 5 min. Then, 1.2 g of EAA and 0.22 g of epoxy compound 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester were added and mixed for 10 min. Finally, 0.54 g of DCP was added and mixed for 3 min to obtain LE 3.0 ED 1.4 Blended composite materials.

[0029] (2) Processing: LE 3.0 ED 1.4 The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 minutes at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 3.0 ED 1.4 High voltage DC cable materials.

[0030] Example 3

[0031] (1) Melt blending: 37.64 g of LDPE was added to a torque rheometer and melted at 115 °C with a rotation speed of 50 r / min. After mixing for 5 min, 2 g of EAA and 0.36 g of epoxy compound 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester were added and mixed for 10 min. Finally, 0.53 g of DCP was added and mixed for 3 min to obtain LE 5.0 ED 1.4 Blended composite materials.

[0032] (2) Processing: LE 5.0 ED 1.4 The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 minutes at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 5.0 ED 1.4 High voltage DC cable materials.

[0033] Embodiment 4:

[0034] (1) Melt blending: 36.69 g of LDPE was added to a torque rheometer, melted at 115 °C, with a rotation speed of 50 r / min, and mixed for 5 min. Then, 2.8 g of EAA and 0.51 g of epoxy compound 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester were added and mixed for 10 min. Finally, 0.51 g of DCP was added and mixed for 3 min to obtain LE 7.0 ED 1.4 Blended composite materials.

[0035] (2) Processing: LE7.0 ED 1.4 The blended composite material was pressed in a flat vulcanizer at a temperature of 115°C and a pressure of 15 MPa, and then pressed for 30 minutes at a temperature of 175°C and a pressure of 15 MPa to complete crosslinking and obtain LE 7.0 ED 1.4 High voltage DC cable materials.

[0036] The performance tests were performed on the LEED high-voltage DC cable materials with different contents prepared in the above Examples 1 to 4, and the specific test results are as follows:

[0037] (1) The molecular structures of the above four materials were tested, analyzed and characterized by Fourier transform infrared spectrometer (FT / IR 6100) to verify whether they successfully participated in the cross-linking reaction. The sample thickness selected in the experiment was 200 μm thin slices, and the test spectrum wave number range was 500-4000 cm -1 , scanning accuracy is 2cm -1 , the scanning times are 30 times, and the results are as follows Figure 1 shown.

[0038] Depend on Figure 1 It can be seen that compared with the EAA / LDPE blend material, the modified high-voltage DC cable material has a -1 A new absorption peak appeared near 1700 cm -1 The peak red-shifted to 1726 cm -1 , and turned into a broad peak, corresponding to the characteristic peak of the ester group in the composite material, indicating that the cross-linking was successful.

[0039] (2) Prepare dumbbell specimens and measure cross-sectional areas according to the test method specified in GB / T 2951.11-2008. Cut the prepared modified high-voltage DC cable material sample into a dumbbell-shaped specimen with a thickness of 1 mm using a cutter. The total length is 75 mm, the width of the effective test part is 4 ± 0.2 mm, and the surface is smooth without visible defects. Use a marker to mark the narrow section with a spacing of 20 mm. The test is carried out in a 200℃ natural ventilation oven. The specimen is suspended from the upper chuck and clamped by the lower chuck. A weight is added to the lower chuck. The weight = 20.4 × specimen thickness × specimen width (including clamps, support rods and weights). The specimen is kept at 200℃ in the oven. After 15 minutes, the distance between the marking lines is measured and the elongation is calculated.

[0040] According to GB / T 12527-2008, the thermal elongation of XLPE insulated cables should not exceed 175%. Figure 2It can be seen that the cable materials prepared in the present invention meet the standards, and the thermal elongation decreases significantly with the increase of EAA. When the EAA content is 7%, the thermal elongation is the lowest, which is only 59.50%.

[0041] (3) The above four materials were tested by SUNS UTM2203 electronic universal testing machine according to the national standard GB / T528-2009. According to the test method required by the standard, the modified LEED composite material specimens were cut into dumbbell-shaped specimens with a thickness of 1 mm using a cutter, with a total length of 75 mm and an effective test portion width of 4 ± 0.2 mm. The surface was smooth without visible defects, and a marker pen was used to mark the narrow section with a spacing of 20 mm. The clamp spacing was set to 20 mm, the tensile rate was set to 250 mm / min, and each material was tested 5 times.

[0042] According to the requirements of standard GB / T 22078.1-2008, the tensile strength and elongation at break of XLPE materials for high-voltage power cables should be no less than 12.5MPa and 200% respectively. Figure 3 It can be seen that under the same experimental conditions, the tensile properties of the modified high-voltage DC cable material meet the required standards, with an elongation at break of 1378.82% and a tensile strength of 28.54 MPa. The elongation at break is 6.89 times higher than the standard, and the tensile strength is 2.28 times higher than the standard.

[0043] (4) The DC breakdown field strength test of the above four materials was carried out at 30°C using cylindrical electrodes, with a voltage step-up rate of 1 kV / s and a sample thickness of 50 μm. The samples and electrodes were all in transformer oil, and 10 groups of samples were selected for repeated experiments under each experimental condition.

[0044] The two-parameter Weibull distribution is used to perform statistics on the DC breakdown strength experimental data, which is described as follows:

[0045] P(E)=1-exp(-(E / E b ) β )

[0046] Where: P(E) is the cumulative failure probability, E is the measured breakdown field strength, E b is the characteristic breakdown field strength when the breakdown probability is 63.2%, and β is the shape parameter.

[0047] The Weibull distribution of the DC breakdown strength of the above four materials is as follows: Figure 4 shown.

[0048] Depend on Figure 4It can be seen that the DC breakdown strength of the four modified high-voltage DC cable materials is improved to varying degrees compared to the unmodified ones. After adding epoxy compounds for modification, the breakdown field strength of each content is significantly improved. The DC breakdown strength of the modified high-voltage DC cable material reaches a maximum value of 476.3kV / mm at 3% EAA content, which is 57.51% higher than that of pure LDPE. The breakdown strength of the commonly available XLPE is 377kV / mm, and the LE 3.0 ED 1.4 The content of this material is 26.34%, which is an increase of 26.34%. The high-voltage DC cable material with this content has good electrical resistance.

[0049] The above description is only a preferred embodiment of the present invention. In view of the fact that technicians in the field of the present invention can make appropriate changes and modifications to the above implementation, the present invention is not limited to the specific implementation described above. Some modifications and changes to the present invention should also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a high voltage DC cable material of 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester and DCP double crosslinked EAA and LDPE, characterized in that A certain amount of low-density polyethylene (LDPE), small molecule 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester, ethylene acrylic acid copolymer (EAA) and dicumyl peroxide (DCP) are added into a torque rheometer for melt blending to obtain a mixed material; the mixed material is pressed and formed in a flat vulcanizer, then heated and cross-linked, and after cooling, a high-voltage DC cable material with significantly improved breakdown strength and tensile properties is obtained.

2. The method for preparing a 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester and DCP double crosslinked EAA and LDPE high voltage DC cable material according to claim 1, characterized in that The components used as the crosslinking agent are small molecule epoxy compounds 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester and diisopropylbenzene peroxide DCP.

3. The method for preparing a 4-(4-epoxymethoxyphenyl) benzoic acid glycidyl ester and DCP double cross-linked EAA and LDPE high voltage DC cable material according to claim 1, characterized in that The mass of EAA is 1%-7% of the total mass of 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester, EAA and LDPE.

4. The method for preparing a 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester and DCP double cross-linked EAA and LDPE high voltage DC cable material according to claim 1, characterized in that The mass of LDPE is 91.72%-98.82% of the total mass of 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester, EAA and LDPE.

5. The method for preparing a 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester and DCP double cross-linked EAA and LDPE high voltage DC cable material according to claim 1, characterized in that The mass of DCP is 1.4% of the mass of LDPE.

6. The method for preparing a 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester and DCP double cross-linked EAA and LDPE high voltage DC cable material according to claim 1, characterized in that The mass of 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester is 0.18%-1.28% of the total mass of 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester, EAA and LDPE.

7. The method for preparing a 4-(4-epoxymethoxyphenyl)benzoic acid glycidyl ester and DCP double cross-linked EAA and LDPE high voltage DC cable material according to claim 1, characterized in that Mainly used in high voltage DC cable materials.

8. The use according to claim 7, characterized in that The prepared high-voltage DC cable material has a DC breakdown strength of up to 476.3 kV / mm and a tensile elongation at break of up to 1130%-1378%.

Citation Information

Patent Citations

  • Multi-layer co-extrusion film material and preparation method thereof

    CN114702915A

  • Preparation and application of epoxy cross-linked LLDPE / EAA composite insulating material

    CN117362693A